HUBUNGAN KEBIASAAN BERMAIN GADGET DENGAN TINGKAT PERKEMBANGAN ANAK USIA 4 – 6 TAHUN DI TK AL FATTAH - Royani Chairiyah; Wa Ode Erty Hikma (Jurnal Education and Development, 2023)
Along with the increasing use of gadgets, the number of gadget addicts also increases, increasing the danger of child development disorders such as motor delays, language delays, and social behavior problems. The purpose of this study was to see if there was a relationship between the behavior of playing gadgets with the level of development of children aged 4-6 years in Al-Fattah Kindergarten. Method: Analytical chi-square statistic test with cross-sectional technique. The overall sampling technique was 50 students using the sampling approach used. Free time, playing gadgets, mother's education, and mother's job are variables. The degree of development of children aged 4-6 years is the dependent variable. Filling out the DDST II form as primary data, with the research period March-June 2020. The p value = 0.000 was obtained, which indicates that there is no significant difference. There is a significant relationship between the use of gadgets and the growth of kindergarten children in Al-Fattah. Conclusion: There is a relationship between the use of gadgets with the development of preschool age children. In order not to interfere with the child's development, parents should limit their child's access to electronic devices